Analysis of innovation adoption decision process among the mechanised fishing boat operators at selected fishing harbours in India - Charles Jeeva, J.; Balasubramaniam, S.; Vasanthakumar, J. (Indian Journal of Fisheries, 2016)
The study was conducted among the large mechanised wooden trawl boat operators involved in marine fishing in three selected major fishing harbours of the country viz., Visakhapatnam in Andhra Pradesh, Thoothukudi in Tamil Nadu and Veraval in Gujarat. The socio-economic and psychological characteristics of fishermen were assessed. The overall innovation decision efficiency index (IDEI) score was 55.25%. The findings on centre-wise and technology-wise IDEI scores are also discussed. The respondents from the three fishing centres differed significantly (p<0.05) in their innovation decision behaviour pertaining to adoption of the technologies viz., FRP sheathing for fishing vessels, marine anticorrosive painting, marine antifouling painting, turtle excluder device (TED), square mesh codend and use of adequate ice onboard. The regression coefficients of four variables viz., investment on fishing craft and gears, innovativeness, training undergone and extent of linkage with research and extension systems significantly and positively influenced the innovation decision process (p<0.05). The R2 value was found to be 0.838, indicating that the 17 characteristics taken together accounted to 83.80% of variations in the innovation decision efficiency level. The constraints in the innovation adoption decision process pertaining to the identified technologies were also documented.